2006
DOI: 10.1029/2006jg000194
|View full text |Cite
|
Sign up to set email alerts
|

Importance of charcoal in determining the age and chemistry of organic carbon in surface soils

Abstract: [1] Understanding the chemical character and turnover time of the oldest soil organic carbon (SOC) fraction is fundamental in deciphering soil carbon sequestration processes and the fate of soil-eroded carbon in aquatic sediments. Two main processes are thought to extend the turnover time of SOC: protection by the mineral matrix and chemical recalcitrance. Various oxidation methods have been proposed to isolate the oldest and most recalcitrant SOC fraction, which is often assumed to be black carbon (BC). Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 38 publications
4
70
1
Order By: Relevance
“…Both factors, the loss of permafrost and more severe burning, are predicted to drive these ecosystems to become net C sources . As mentioned in the section on recalcitrance, grasslands in Australia with frequent fires have relatively high proportions of chemically recalcitrant black carbon (Krull et al 2006). Changes in fire frequency linked to climate or land management may ultimately control a region's status as a C source or sink.…”
Section: Disturbancementioning
confidence: 99%
See 2 more Smart Citations
“…Both factors, the loss of permafrost and more severe burning, are predicted to drive these ecosystems to become net C sources . As mentioned in the section on recalcitrance, grasslands in Australia with frequent fires have relatively high proportions of chemically recalcitrant black carbon (Krull et al 2006). Changes in fire frequency linked to climate or land management may ultimately control a region's status as a C source or sink.…”
Section: Disturbancementioning
confidence: 99%
“…Black carbon, organic matter transformed by pyrolization, remains a candidate for recalcitrance. Comparing a grassland, woodland, and subtropical rainforest in Australia, Krull et al (2006) concluded that although the woodland and rainforest had greater aggregate and mineral protective capacity, respectively, the grassland supported a larger reservoir of more stable carbon due to frequent inputs of charcoal from regular fires. In a Russian…”
Section: Recalcitrancementioning
confidence: 99%
See 1 more Smart Citation
“…Intrinsic recalcitrance: While all organic carbon is ultimately thermodynamically unstable, soils contain a number of compounds that may be difficult to decompose owing to their specific chemical structure. Pyrolized carbon formed in fire can be one example (Krull et al 2006b, Preston & Schmidt 2006; some lipid compounds are also extremely long-lived in soil (Mikutta et al 2006). …”
Section: Mechanisms For Stabilizing Carbonmentioning
confidence: 99%
“…In contrast, biomass-derived black carbon (C), or biochar, is much more stable. While biochar must eventually mineralize in soil (Goldberg 1985;Schmidt and Noack 2000), a fraction remains in a very stable form with a 14 C age greater than that of the oldest soil organic matter (SOM) fractions (Krull et al 2006;Pessenda et al 2001;Skjemstad et al 1996).…”
Section: Introductionmentioning
confidence: 99%